Method for calculating actual capacity of single-stage long-stroke reciprocating compressors - V. L. Yusha; S. S. Busarov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article presents a generalized method for calculating the actual performance of low-speed long-stroke air compressor stages of compression, based on determining the flow rate as a set of coefficients reflecting the influence of various factors on productivity losses. The method takes into account the design and operating features of low-speed long-stroke air compressor stages of compression and differs significantly from a similar method used to calculate high-speed stages of reciprocating compressors